Functional Outcome of Hydrodilatation Versus Intra-Articular Corticosteroid Injection in Patients with Frozen Shoulder. - Kamran Asghar , Tahreen Ahmad , Nouman Maqbool, Kamran Asghar , Tahreen Ahmad , Nouman Maqbool (Journal of Rawalpindi Medical College, 2018)
Background : To compare hydrodilatation with intra-articular injection of corticosteroid in patients with frozen shoulder. Methods: In this comparative study a total of 80 patients with frozen shoulder were divided into two groups. Patients in group A were treated with hydrodilatation under local anaesthesia . The joint capsule was distended by injecting 40 ml of normal saline. Patient was observed for 30 min and then assisted range of motion and supervised active exercises were performed. Group B patients were treated with intra-articular steroid (triamcinolone acetate) 40 mg along with 1 ml of 1 % w/v of lidocaine . The patient was advised to do shoulder exercises from the next day, three times a day along with oral non-narcotic analgesics. Patients were evaluated by recording pre-procedure pain scoring and range of motion and post-procedure scoring at 4 weeks after the procedure. Effectiveness was taken as improvement in the final score of at least 9 (pain improvement of 5 and ROM score of 4) or more at four weeks follow up. Results: Majority (60.62%) were male. Group A patients had mean pre procedure score of 9.87± 4.44 and post procedure score was 22.8± 5.14, while in group B, pre procedure score was 9.78± 4.49 and post procedure score was 21.49± 5.56. Out of 80 patients in group A, the effectiveness was observed in 92.50%, while in group B patients had effectiveness in 73.75%. The chi square test showed the p-value of 0.003, which was quite significant. Conclusion: Hydrodilatation was found to be effective and convenient outpatient department procedure with better functional outcome, at four weeks follow up, than corticosteroid injection alone.